THE ROLE OF WORK MOTIVATION AS AN INTERVENING VARIABLE BETWEEN EMPLOYEE COMPETENCE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Putra, Muhammad Ramadhan; Prahiawan, Wawan; Damarwulan, Liza Mumtazah (jfpublisher, 2025)
This study examined the relationship between competence and work environment on employee performance, with work motivation functioning as a mediating factor. The study was implemented at Cilegon City's Environmental Office (Dinas Lingkungan Hidup) through a quantitative research design utilizing questionnaire surveys administered to 62 participants. Data analysis employed Structural Equation Modeling (SEM) via Partial Least Squares (PLS) methodology, processed through SmartPLS 4 software. Results revealed that work environment demonstrates significant influence on work motivation, while work motivation exhibits significant impact on employee performance. Notably, competence and work environment failed to demonstrate direct significant effects on performance outcomes. The mediating analysis showed that work motivation does not significantly mediate the competence-performance relationship, yet effectively mediates the work environment-performance relationship. These results highlight the critical importance of fostering supportive workplace conditions to strengthen employee motivation, which subsequently enhances performance outcomes. The research proposes actionable recommendations including improvements to physical and social workplace infrastructure, implementation of psychological support mechanisms, and establishment of non-monetary incentive frameworks. This study advances knowledge in public sector human resource management practices, particularly by demonstrating motivation's pivotal role in connecting work environment factors with employee performance achievements.